Viral infection in wheezy bronchitis and asthma in children. Issue 9 (September 1976) - Mitchell I'Inglis, H; Inglis, H; Simpson, H
Abstract : Virus isolation was attempted on 267 out of 360 patients with wheezy bronchitis or asthma admitted to hospital during a 3-year period. Viruses were isolated on 39 occasions, the most common being respiratory syncytial virus and rhinovirus. The peak months for virus isolation were February and August. Virus isolation was significantly more common in readmissions than in first admissions (P less than 0-01). Viruses were isolated in both sexes throughout childhood and though the admission rate fell with increasing age, the isolation rate was unaffected. The possible significance of viral infection as a cause of acute attacks of wheezing in children is discussed.